Indian Stock Market-Hedging of "Index Future" is a Boon or Bane - Buvaneswari, R. P.; Mani, A.; Ragupathi, Dr. M.; Kirubakaran, M. (Indian Journal of Finance, 2007)
Investment on securities such as shares, debentures, bonds are profitable as well as exciting. It is indeed rewarding but involves a great deal of risk. It is acknowledged to be one of the most risky avenues for investment. Risk reduction is significant for the investor as it is directly related to the return of the investments. Some of the risk management technologies that can be used in the capital market now days are: Risk Avoidance, Combination, Diversification, Risk Transfer, Portfolio Investment, and Hedging.